Togo : Assessment Letter for the World Bank. (Policy Papers; Policy Paper ;, 2009)
This note provides the IMF staff assessment of recent macroeconomic developments in Togo and progress under the Fund-supported three-year Poverty Reduction and Growth Facility program (PRGF) starting from January 2008 based on preliminary information through end-December 2008.